2017
DOI: 10.5535/arm.2017.41.2.290
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Radial Motor Nerve Conduction Study Using Ultrasound in Healthy Adults

Abstract: ObjectiveTo obtain reference values, to suggest optimal recording and stimulation site for radial motor nerve conduction study (RmNCS), and to analyze the correlation among RmNCS parameters, demographics and ultrasonography (US) findings.MethodsA total of 55 volunteers participated in this study. We hypothesized that ‘lateral edge of spiral groove (A)’ was the optimal stimulation site, and the ‘largest cross-sectional area (CSA) of extensor indicis proprius (EIP) muscle (B)’ was the optimal recording site. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The needle can be placed in the extensor digiti minimi or extensor carpi ulnaris after superficial insertion or the pronator quadratus after deep insertion [ 13 , 16 ]. Third, because the EI is not clearly separated from other muscles that are innervated by the radial nerve, it is difficult to distinguish the EI from other muscles [ 17 ]. Due to the characteristics of the EI, a muscle contraction is often induced to identify the location of the muscle and insert the needle exactly.…”
Section: Discussionmentioning
confidence: 99%
“…The needle can be placed in the extensor digiti minimi or extensor carpi ulnaris after superficial insertion or the pronator quadratus after deep insertion [ 13 , 16 ]. Third, because the EI is not clearly separated from other muscles that are innervated by the radial nerve, it is difficult to distinguish the EI from other muscles [ 17 ]. Due to the characteristics of the EI, a muscle contraction is often induced to identify the location of the muscle and insert the needle exactly.…”
Section: Discussionmentioning
confidence: 99%
“…The active recording sites were determined based on textbooks of radial motor nerve conduction study using the extensor indicis muscle and the results of our cadaver study: two fingerbreadths proximal to the USP (Method 1) (approximately 3 cm proximal to the USP) 4,9 ; the distal 1/4 point of the forearm length (Method 2) based on the results of our cadaveric study; and the most prominent site during activation of the extensor indicis, which is frequently used in clinical practice (approximately 1 cm to 1.5 cm proximal to the recording electrode site of Method 2) (Method 3) 9 . Reference recording electrodes were located at two sites: the USP (A), as recommended by textbooks and a previous study 1,4,8,9 ; or the tendon of the extensor indicis muscle at the level of the USP (B), according to the belly‐tendon method 4 . The onset latency and baseline‐to‐peak amplitude of the compound muscle action potentials (CMAPs) were measured.…”
Section: Methodsmentioning
confidence: 99%
“…In studies using the extensor indicis muscle, the recommended location of the E1 electrode is two fingerbreadths or 2 to 4 cm proximal to the ulnar styloid process (USP) 4,9 . In contrast, a recent study using ultrasonography recommended placing the E1 electrode over a point in the distal 20% of the forearm 1 …”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…High‐resolution ultrasonography (US) is regarded as an effective tool in assessing the peripheral nerves of the limbs 4‐9 . Several studies have demonstrated the utility of US‐guided NCSs in more accurately applying stimulation or placing recording electrodes, particularly with regard to the lower limb nerves 10‐12 . While this focus has been on the lower limbs, upper limb nerve injuries are common, and certain nerves are at a higher risk for injury due to their anatomic locations 13 .…”
Section: Introductionmentioning
confidence: 99%